PENGARUH STRES KERJA DAN MOTIVASI TERHADAP KEPUASAN DAN KINERJA KARYAWAN PT PLN (PERSERO) AREA MERAUKE - Dewi Putri Anjar Wulan; Syamsu Alam; Fauziah Umar (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2018)
One of the organizational resources that has an important role in achieving its objectives is human resources. This study aims to determine to determine the effect of Stress Work and Motivation Against Satisfaction and Employee Performance PT PLN (Persero) Area Merauke. The type of research used in this study is quantitative approach. The quantitative approach is based on the approach done by recording and analyzing the data of the research results by using statistical calculations supported by literature study and data collection tool in the form of questionnaires distributed to employees of PT PLN (Persero) Merauke Area. The results showed that partially between work stress and work motivation have positive and significant effect to job satisfaction, work stress and work motivation have positive and significant influence to employee performance, as well as job satisfaction have positive and significant effect to employee performance. As for the indirect influence indicates that job satisfaction can mediate the effect of work stress and work motivation on employee performance. Keywords: Work Stress, Work Motivation, Job Satisfaction,, Employee Performance